2023
DOI: 10.3389/fmicb.2023.1165631
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizer based on halotolerant microorganisms promotes the growth of rice plants and alleviates the effects of saline stress

Abstract: Long-term soil salinization easily contributes to soil hardness, soil nutrient imbalance, and soil microbial diversity reduction, resulting in low rice yields in the salinized fields, and microbial remediation is one of the important measures to improve salinized soil. To verify the effect of biofertilizer based on halotolerant microorganisms on promoting rice growth and alleviating saline stress, this study discussed the effects of biofertilizer on soil microbial diversity and community structure and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Salt stress affects potential functions such as microbial metabolism and material cycling in plant rhizosphere soils [ 43 ]. In this study, salt stress increased the relative abundance of rhizosphere bacterial carbon and sulfur cycle groups in T. chinensis , and it has been shown that changes in the carbon cycle group are more pronounced in the rhizosphere in response to salinity stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress affects potential functions such as microbial metabolism and material cycling in plant rhizosphere soils [ 43 ]. In this study, salt stress increased the relative abundance of rhizosphere bacterial carbon and sulfur cycle groups in T. chinensis , and it has been shown that changes in the carbon cycle group are more pronounced in the rhizosphere in response to salinity stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sediment contains a large amount of oxidized and well-decomposed organic matter owing to microbial activity [21]. The organic substances are decomposed and/or oxidized by bacteria, and nutrients such as N, phosphorus, and potassium are released under appropriate conditions [22]. In addition to organic matter and a large amount of available nutrients, sediment is also rich in trace elements such as calcium, iron, manganese, copper, zinc, boron, magnesium, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an increase in the special bacterial groups: Bryobacter, Xanthobacteriaceae, and Gemmatimonas can reduce the effective Cd content in rice fields [13]. Halotolerant microorganisms Agrobacterium tumefaciens, Bacillus subtilis, and Lysinibacillus fusiformis alleviate saline stress in rice, thus promoting rice growth in the salinized field [14,15]. Endophytic seed-associated bacteria (Pantoea sp.…”
Section: Introductionmentioning
confidence: 99%